An Exploration of University Students' Experience Using UI-UX Based E-learning Platforms: Challenges and Recommendations - Mujiono, Mujiono; Wibowo, Tangguh Okta; Alvin, Silvanus (International Journal of Social Learning (IJSL), 2025)
This study explores the optimization of User Interface (UI) and User Experience (UX) in e-learning platforms to enhance user engagement and satisfaction. Using a qualitative case study approach, observations and interviews were conducted to identify user challenges. The findings reveal that an intuitive UI and positive UX significantly improve the efficiency of online learning. However, issues such as server reliability and accessibility barriers for students with disabilities remain challenges. This study highlights the need for inclusive and responsive UI/UX design to foster an effective online learning ecosystem. Recommendations are provided for platform developers to address these shortcomings, ensuring a more accessible and seamless experience for students, educators, and administrators, particularly in higher education. The results serve as a foundation for further improvements in e-learning platform design and implementation.